Constitutional Debate on European Union’s Shifting Pathway towards Supranationalism (Universitas Negeri Semarang, 2022)
The rapid evolution of the European Union (EU) has suggested a new debate on regionalism due to the institutional transformation from intergovernmentalism to supranationalism. Hitherto, the EU has undergone a shifting pathway as a supranational institution that raises a further debate on supranational constitutionalism. This paper aimed to critically examine the EU's legal capacity for external relations at the World Trade Organization (WTO) following in identifying the impact of the EU member states to become members of this world institution as well. However, new approaches were considered within the shifting paradigm, which includes supranational union as an emerging pivotal global actor in international relations. This paper showed that the emergence of EU supranationalism has challenged the traditional debate on state sovereignty rooted in the Westphalian concept, particularly against the state primacy in international law. While the EU regionalism contributed to legal conversation both in the regional and international arena, the juxtaposition of the state and the supranational 'state' has increasingly blurred their limits, becoming sui generis in regionalism and state discourses among the areas of international law and constitutional law.